TRANSFORMATION OF RUKYATUL HILAL METHOD (Postmodernism Analysis of Hilal Image Processing) - Riza Afrian Mustaqim (Fakultas Syari'ah dan Hukum UIN Walisongo, 2019)
The usage of devices in performing of rukyat al-hilâl whose function is to make objects (hilāl) from outer space appear as bright, contrasty and large as possible isnot direcly give a solution. The view of fiqh on using devices in rukyat al-hilâl become an obstacle in the development of the rukyat method with technology. The technology of rukyat al-hilâl is improving rapidly and developing significantly, in reverse with it’s legal developments. Therefore, there must be a transformation of the rukyat al-hilâl method as well as development of the times, without leaving it’s validity to fiqh. This study analyzes the views of postmodernism in hilal image processing. This research focuses on hilal images processing in the view of postmodernism. The research method used was library research with descriptive analysis. The results show that first, postmodernism considers that image processing is a development of method in rukyat al-hilâl that is needed. This is caused by limitations in the current method that has not been able to provide a solution, but the use of technology in rukyat should not leave its validity according to fiqh. Second, Restrictions on using devices in rukyat al-hilâl will obstruct it's main purpose which is to confirm the existence of the new moon and blocked the broadest development opportunities as a form of subjectivity and a plurality of knowledge.